PENGARUH KEPERCAYAAN DAN PERSEPSI RESIKO TERHADAP KEPUTUSAN PEMBELIAN ONLINE OLEH MAHASISWA: STUDI KASUS PADA MAHASISWA STIE AKA SEMARANG - Riyono, Riyono; Astono, Ari Dwi; M, Rosiana Novitasari (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
The purpose of this study was to determine how much influence the trust and risk perceptions of online purchasing decisions, the population in this study were all STIE AKA Semarang students who were still active in the 2017/2018 Academic Year on Campus I. The study was conducted by sampling, purposive technique sampling, obtained a sample of 100 people. The analysis technique used is multiple linear regression. The results of the study can be concluded that: 1) Trust has a positive effect on online purchasing decisions, 2). Perception of risk has a negative effect on online purchasing decisions.